2016
DOI: 10.1115/1.4034461
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Energy Dissipation in Wavy Surfaces

Abstract: Accurate estimation and tuning of frictional damping are critical for proper design, safety, and reliability of assembled structures. In this study, we investigate how surface geometry and boundary conditions affect frictional energy dissipation under microslip contact situations. In particular, we investigate the frictional losses of a two-dimensional (2D) deformable wavy surface in contact with rigid plate under specific normal and tangential loading. We also propose a dissipation tuning mechanism by tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…High normal load pressures led to the suppression of sliding, whereas low pressures promoted frictional slip behavior; noticeably, Opadry ® EZ most effectively imparted lubricity in comparison to other formulations, as observed in Figure 4 . The literature has demonstrated that polysaccharide gums such as xanthan, carrageenan, guar, and konjac gum possess unique abilities to dissipate frictional energies through their saccharide side branch structures due to the greater extent of coil–helix transformation that imbibes superior volumes of water, creating thin aqueous sheets for improved gliding [ 65 , 66 , 67 ]. Furthermore, the results confirmed that the critical shear force needed to initiate lateral motion of binary film-coated tablets in comparison to uncoated, KIR, HPMC, or PVA-coated tablets was greater than the minimum transitional force of the common, aforementioned commercial coating systems, an indication of the least resistant wet slip behavior.…”
Section: Resultsmentioning
confidence: 99%
“…High normal load pressures led to the suppression of sliding, whereas low pressures promoted frictional slip behavior; noticeably, Opadry ® EZ most effectively imparted lubricity in comparison to other formulations, as observed in Figure 4 . The literature has demonstrated that polysaccharide gums such as xanthan, carrageenan, guar, and konjac gum possess unique abilities to dissipate frictional energies through their saccharide side branch structures due to the greater extent of coil–helix transformation that imbibes superior volumes of water, creating thin aqueous sheets for improved gliding [ 65 , 66 , 67 ]. Furthermore, the results confirmed that the critical shear force needed to initiate lateral motion of binary film-coated tablets in comparison to uncoated, KIR, HPMC, or PVA-coated tablets was greater than the minimum transitional force of the common, aforementioned commercial coating systems, an indication of the least resistant wet slip behavior.…”
Section: Resultsmentioning
confidence: 99%
“…is phenomenon can be due to the fact that the enriched porosity of cement mortar led to the increase of energy dissipation [33]. In addition, the loose contact between DSP/CNF-EG and cement matrix could cause the interface friction action, also dissipating a lot of energy under the vibration load [39]. Based on the obtained storage modulus and loss modulus, the loss tangent of the samples can be calculated by using the following equation [40]:…”
Section: Damping Properties Of Dsp/cnf-eg/cmmentioning
confidence: 99%